Penerapan Sistem Informasi Akuntasi Penggajian dan Pengupahan Karyawan pada PT.TSM Surabaya - Alfida Dwi Sulistyowati; Wiratna Wiratna; Heri Toni P; Tjandra Wasesa; Diana Zuhroh (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This research is a qualitative study that utilizes both primary and secondary data sources. It was conducted at PT. TSM in Surabaya, a company engaged in buying and selling car spare parts. The primary aim of this research is to examine the application of the employee payroll and wage accounting information system at PT. TSM Surabaya. The results of this study indicate that the company’s method of calculating salaries and wages for employees still does not utilize an effective accounting system, which is not aligned with established theories. Additionally, the company relies on manual salary calculations, which creates inefficiencies and errors in the payroll process. The absence of a computerized payroll system highlights a significant gap in the company's operational processes. This manual approach poses challenges in terms of accuracy, speed, and transparency, which could potentially affect employee satisfaction and overall business performance. The research further reveals that the company has not yet implemented automated or integrated payroll systems that could improve the accuracy and efficiency of the payroll process. In conclusion, this study suggests the need for PT. TSM Surabaya to adopt an automated payroll system, in line with industry standards, to enhance operational efficiency, minimize human errors, and ensure timely and accurate employee compensation. This could help the company stay competitive and improve its financial management practices.